Comparative pharmacokinetics of cefuroxime lysine after single intravenous, intraperitoneal, and intramuscular administration to rats - Zhao Long-shan; Yin Ran; Wei Bin-bin; Li Qing; Jiang Zhen-yuan; Chen Xiao-hui; Bi Kai-shun (Acta Pharmacologica Sinica, 2016)
Aim: To compare the pharmacokinetic parameters of cefuroxime lysine, a new second-generation of cephalosporin antibiotics, after intravenous (IV), intraperitoneal (IP), or intramuscular (IM) administration. Methods: Twelve male and 12 virgin female Sprague-Dawley rats, weighing from 200 to 250 g, were divided into three groups (n=4 for each gender in each group). The rats were administered a single dose (67.5 mg/kg) of cefuroxime lysine via IV bolus or IP or IM injection. Blood samples were collected and analyzed with a validated UFLC-MS/MS method. The concentration-time data were then calculated by compartmental and non-compartmental pharmacokinetic methods using DAS software. Results: After IV, IP or IM administration, the plasma cefuroxime lysine disposition was best described by a tri-compartmental, bi-compartmental or mono-compartmental open model, respectively, with first-order elimination. The plasma concentration profiles were similar through the 3 administration routes. The distribution process was rapid after IV administration [t1/2(d), 0.10±0.11 h vs 1.36±0.65 and 1.25±1.01 h]. The AUMC0–∞ is markedly larger, and mean residence time (MRT) is greatly longer after IP administration than that in IV, or IM routes (AUMC0–∞: 55.33±20.34 vs 16.84±4.85 and 36.17±13.24 mg·h2/L; MRT: 0.93±0.10 h vs 0.37±0.07 h and 0.65±0.05 h). The Cmax after IM injection was significantly higher than that in IP injection (73.51±12.46 vs 49.09±7.06 mg/L). The AUC0–∞ in male rats were significantly higher than that in female rats after IM administration (66.38±16.5 vs 44.23±6.37 mg·h/L). There was no significantly sex-related difference in other pharmacokinetic parameters of cefuroxime lysine between male and female rats. Conclusion: Cefuroxime lysine shows quick absorption after IV injection, a long retension after IP injection, and a high Cmax after IM injection. After IM administration the AUC0–∞ in male rats was significantly larger than that in female rats.